Aerobic exercise in older people with subclinical sporadic cerebral small vessel disease: A randomized clinical trial. Issue 1 (31st December 2021) - Wong, Adrian; Lam, Bonnie Yin Ka; Mak, Margaret Kit Yi; Lam, Linda Chiu Wa; Au, Lisa Wing Chi; Yiu, Brian Ka Fung; Wong, Chun; Tong, Hor Yee; Yeung, Sin Ki; Chu, Winnie Chiu Wing; Shi, Lin; Leung, Thomas Wai Hong; et al.
Abstract: Introduction: The benefit and risk of aerobic exercise among older people harboring advanced cerebral small vessel disease (CSVD) upon cognition, mood, and motor functions are unknown. Methods: This rater‐blind randomized trial examined effects of a 24‐week aerobic exercise training (60 min/session, twice/week) upon clinical (cognition, mood, motor functions) and hemodynamic (pulse pressure [PP], blood pressure [BP], pulsatility index) measures in older people harboring moderate to severe CSVD, as evidenced by confluent white matter hyperintensity and/or ≥2 lacunes on magnetic resonance imaging. We further investigated interactions between treatment conditions and hemodynamics measures. Results: Fifty‐three and 54 subjects were randomized into the active and control group, respectively. There was no between‐group difference in any of the clinical outcomes. The active group had a greater between‐group reduction in systolic BP and PP than the control group. Within‐group comparison showed that global cognition of the active group remained similar at end of the study compared to baseline, whereas it declined significantly in the control group. We observed "diverging" interaction effects in that greater reduction in systolic BP/PP was associated with greater improvement in memory functions and global cognition but worsening in processing speed in the active group. Side effects were comparable between the two groups. Discussion: Future study should investigate the mechanisms of the diverging impacts of aerobic exercise upon different cognitive domains so that the benefit–risk ratio of aerobic exercise in older people harboring more advanced CSVD can be better defined.